The peculiar problem of taxing life insurance companies : a staff paper - Aaron, Henry J. (Washington, D.C. : Brookings Institution, 1983)
The paper examines the tax treatment of life insurance companies.
Includes bibliographical references.
obn 23/01/2019
Loans
Keywords: Life insurance